Modern Technologies for Creating the Thin-Film Systems and Coatings 2017
DOI: 10.5772/66921
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of P3AT Films Used as a Probe of Optical Properties in Polymeric System

Abstract: Poly(3-alkylthiophene) (P3ATs) have been extensively used in photovoltaic devices such as a p-type organic Semiconductors. However, several electronic properties of P3ATs present energy transfer inter-and intra-chains that have direct consequences on the performance of optoelectronic devices. Traditionally electrochemical techniques, such as cyclic voltammetry, chronoamperometry and chronocoulometry, have been applied to process polymer thin ilms and unconventional spectroscopy techniques are used to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The uniformity of the deposited film can easily be controlled by adjusting the voltage and precursor concentration whereas the film thickness can be controlled by changing the time duration for which the pulse has been applied. In a work done by Soares de Sá et al, chronoamperometric method of polythiophene (organic) film deposition led to uniform films which found applications in organic devices [42]. Similarly in another work by Kim et al, CdS (inorganic) films were electrodeposited which were found to be compact and crystalline [43].…”
Section: Introductionmentioning
confidence: 96%
“…The uniformity of the deposited film can easily be controlled by adjusting the voltage and precursor concentration whereas the film thickness can be controlled by changing the time duration for which the pulse has been applied. In a work done by Soares de Sá et al, chronoamperometric method of polythiophene (organic) film deposition led to uniform films which found applications in organic devices [42]. Similarly in another work by Kim et al, CdS (inorganic) films were electrodeposited which were found to be compact and crystalline [43].…”
Section: Introductionmentioning
confidence: 96%